Deploying Disclosure Laws to Eliminate Forced Labour: Supply chain transparency efforts of Brazil and the United States of America - Feasley, Ashley (Anti-Trafficking Review, 2015)
States are increasingly addressing forced labour in supply chains by implementing transparency or disclosure measures that aim to make companies disclose the existence of forced labour in their supply chains. Examining the recent approaches of Brazil and the United States of America shows some promising practices to best inform governmental policy going forward.